CDKs family -a glimpse into the past and present: from cell cycle control to current biological functions - Shah, Muzna; Qureshi, Muhammad Fazal Hussain; Mohammad, Danish; Lakhani, Mahira; Urooj, Tabinda; Mushtaq, Shamim (Asian Pacific Journal of Cancer Biology, 2020)
Cyclin-dependent kinases (CDKs) are the catalytic subunits or protein kinases characterized by separate subunit “cyclin” that are essential for their enzymatic activity. CDKs play important roles in the control of cell cycle progression, cell division, neuronal function, epigenetic regulation, metabolism, stem cell renewal and transcription. However, they can accomplish some of these tasks independently, without binding with cyclin protein or kinase activity. Thus, so far, twenty different CDKs and cyclins have been reported in mammalian cells. The evolutionary expansion of the CDK family in mammals led to the division of CDKs into three cell-cycle-related subfamilies (Cdk1, Cdk4 and Cdk5) and five transcriptional subfamilies (Cdk7, Cdk8, Cdk9, Cdk11 and Cdk20). In this review, we summarizes that how CDKs are traditionally involve their latest revelations, their functional diversity beyond cell cycle regulation and their impact on development of disease in mammals.